Neuroprotective Riluzole-Releasing Electrospun Implants for Spinal Cord Injury - Ullrich, Mathilde M; Pulipaka, Bhavana; Yin, Jing; Hlinková, Jana; Zhang, Fangyuan; Chan, Michael W; O'Brien, Fergal J; Dervan, Adrian; Dziemidowicz, Karolina (Molecular pharmaceutics, 2025)
Spinal cord injury (SCI) results in paralysis, driven partly by widespread glutamate-induced secondary excitotoxic neuronal cell death in and around the injury site. While there is no curative treatment, the standard of care often requires interventive decompression surgery and repair of the damaged dura mater close to the injury locus using dural substitutes. Such intervention provides an opportunity for early and local delivery of therapeutics directly to the injured cord via a drug-loaded synthetic dural substitute for localized pharmacological therapy. Riluzole, a glutamate-release inhibitor, has shown neuroprotective potential in patients with traumatic SCI, and therefore, this study aimed to develop an electrospun riluzole-loaded synthetic dural substitute patch suitable for the treatment of glutamate-induced injury in neurons. A glutamate-induced excitotoxicity was optimized in SH-SY5Y cells by exploring the effect of glutamate concentration and exposure duration. The most effective timing for administering riluzole was found to be at the onset of glutamate release as this helped to limit extended periods of glutamate-induced excitotoxic cell death. Riluzole-loaded patches were prepared by using blend electrospinning. Physicochemical characterization of the patches showed the successful encapsulation of riluzole within polycaprolactone fibers. A drug release study showed an initial burst release of riluzole within the first 24 h, followed by a sustained release of the drug over 52 days to up to approximately 400 μg released for the highest loading of riluzole within fiber patches. Finally, riluzole eluted from electrospun fibers remained pharmacologically active and was capable of counteracting glutamate-induced excitotoxicity in SH-SY5Y cells, suggesting the clinical potential of riluzole-loaded dural substitutes in counteracting the effects of secondary injury in the injured spinal cord.
Keywords: neuroprotektivní látky; Cell Line, Tumor; riluzol; Neuroprotective Agents; neurony; Riluzole; Glutamic Acid; Animals; lidé; Spinal Cord Injuries; Humans; poranění míchy; zvířata; Neurons; Drug Liberation; implantované léky; Drug Implants; Polyesters; uvolňování léčiv; nádorové buněčné linie; kyselina glutamová; polyestery